2023
DOI: 10.3389/fimmu.2023.1138818
|View full text |Cite
|
Sign up to set email alerts
|

A novel multi-component protein vaccine ECP001 containing a protein polypeptide antigen nPstS1 riching in T-cell epitopes showed good immunogenicity and protection in mice

Abstract: Tuberculosis (TB) is an infectious disease that seriously affects human health. Until now, the only anti-TB vaccine approved for use is the live attenuated Mycobacterium bovis (M. bovis) vaccine — BCG vaccine, but its protective efficacy is relatively low and does not provide satisfactory protection against TB in adults. Therefore, there is an urgent need for more effective vaccines to reduce the global TB epidemic. In this study, ESAT-6, CFP-10, two antigens full-length and the T-cell epitope polypeptide anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…In some of these groups, it occurred that the corresponding antibody titers of the Pa + Tr group were higher than the Pa and Tr groups at the same time point, and we speculate that there is certain synergistic effect between Pa and Tr antigens in terms of immune activation thereby increasing the antibody titers. This is consistent with previous findings that subunit vaccines, constructed by mixing or fusing multiple proteins and combining them with adjuvants, resulted in increased antibody titers as well as functional antibody activity observed in mice [ 39 , 40 ]. Furthermore, The IgG antibody isotype results showed that the IgG1/IgG2a ratios were all greater than 1, suggesting a Th2 response bias [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…In some of these groups, it occurred that the corresponding antibody titers of the Pa + Tr group were higher than the Pa and Tr groups at the same time point, and we speculate that there is certain synergistic effect between Pa and Tr antigens in terms of immune activation thereby increasing the antibody titers. This is consistent with previous findings that subunit vaccines, constructed by mixing or fusing multiple proteins and combining them with adjuvants, resulted in increased antibody titers as well as functional antibody activity observed in mice [ 39 , 40 ]. Furthermore, The IgG antibody isotype results showed that the IgG1/IgG2a ratios were all greater than 1, suggesting a Th2 response bias [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“… 37 , 38 Thus, it has been widely used for the early evaluation of TB vaccine efficacy. 39 , 40 In our study, we found that vaccination with rBCG-ECD003 greatly enhances the ability of spleen lymphocytes to control Mtb growth in the long term. We observed a nearly 1.6-fold reduction in CFU compared to the BCG group.…”
Section: Discussionmentioning
confidence: 54%